2005
DOI: 10.1007/s00468-005-0433-4
|View full text |Cite
|
Sign up to set email alerts
|

Callus cultures and bark from Norway spruce clones show similar cellular features and relative resistance to fungal pathogens

Abstract: In field experiments, clones of Norway spruce [Picea abies (L.) Karst.] showed different degrees of resistance against pathogenic fungi inoculated into the bark that correlate with differences in polyphenolic parenchyma (PP) cells of the bark. Cells of spruce callus cultures, particularly towards the callus surface, resemble PP cells and this study looks at changes in callus cells during infection and the relative resistance of cultures from clones of low (weak) or high (strong) resistance to fungal infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Clone 471 has strong, but not complete resistance to C. polonica infection, as determined by phloem lesion length following experimental inoculation (Nagy et al, 2005). It shows up-regulation of the phenylpropanoid pathway in the phloem following both fungal infection and mechanical wounding (Koutaniemi et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Clone 471 has strong, but not complete resistance to C. polonica infection, as determined by phloem lesion length following experimental inoculation (Nagy et al, 2005). It shows up-regulation of the phenylpropanoid pathway in the phloem following both fungal infection and mechanical wounding (Koutaniemi et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…(2000) evaluated the growth reactions of 27 Scots pine embryogenic cell lines to Gremmeniella abietina , the Scleroderris canker fungus. Nagy et al. (2005) found that the embryogenic cell lines of Picea abies responded to Ceratocystis polonica , the blue-stain fungal pathogen, and Heterobasidion annosum , the butt rot pathogen, in a manner similar to that of trees with varying susceptibility to these diseases.…”
Section: Introductionmentioning
confidence: 97%
“…Similarly, Terho et al (2000) evaluated the growth reactions of 27 Scots pine embryogenic cell lines to Gremmeniella abietina, the Scleroderris canker fungus. Nagy et al (2005) found that the embryogenic cell lines of Picea abies responded to Ceratocystis polonica, the bluestain fungal pathogen, and Heterobasidion annosum, the butt rot pathogen, in a manner similar to that of trees with varying susceptibility to these diseases. Furthermore, Hashmi et al (1993) investigated the response of peach cultures to Meloidogyne incognita, the root-knot nematode, and identified several that exhibited greater resistance than the parental cells.…”
Section: Introductionmentioning
confidence: 97%
“…Although the resistance of the culture could not be demonstrated, a difference in growth rates and glucosamine levels formed in response to fungal infection were detected between the cell lines. Nagy et al treated embryogenic cell lines of Picea abies with spores of the blue-stain fungal pathogen Ceratocystis polonica and the butt rot pathogen Heterobasidion annosum [46]. The response of cell cultures was similar to trees which differ in susceptibility to these diseases.…”
Section: Introductionmentioning
confidence: 99%